Pengujian Perangkat Lunak Berstandar ISO/IEC 29119 pada Aplikasi Sistem Absensi “SIKARYAWAN” Berbasis Website - Putra Zahwa Pratama; Achmad Febriyadi; Chairul Anwar (CV. Multi Kreasi Media, 2025)
The development of web-based attendance systems requires functional quality assurance to ensure that employee attendance data is recorded accurately and transparently. This study aims to evaluate the quality of the